Role of additives in silica-supported polyethylenimine adsorbents for CO2 adsorption - Qianxi Fang; Weiqiu Huang; Hongning Wang (Materials Research Express, 2020)
SiO _2 aerogels were prepared by sol-gel method and methyl alkylation reaction using TEOS as silicon sources. Silica-supported polyethylenimine (PEI/SiO _2 ) adsorbents for CO _2 adsorption were prepare by grafting techniques, in which mesoporous SiO _2 aerogel was loaded with PEI and organic compounds functionalized by hydroxyl or amino groups as dopants. CO _2 adsorption isotherms of PEI amine-modified SiO _2 aerogels were measured and the results show that the maximum CO _2 adsorption capacity (1.8 mmol g ^−1 ) was obtained over a doped SA-PEI-N-Y loaded with 45% PEI and 15% N-Y (N-[3-(Trimethoxysilyl)propyl]ethylenediamine, denoted as N-Y). In addition, SA-PEI-N-Y has stronger thermal stability than SA-PEI-60% in nitrogen from room temperature to 800 °C at a heating rate of 10 °C min ^−1 . It turns out that N-[3-(Trimethoxysilyl)propyl]ethylenediamine is the best dopant.